Comparison of alcohol free GSH production by ultrasonic and homogenizing method - Mohamed Salleh, Mohamad Ramlan; Jamal, Parveen; Gad, Abd. Elaziem Farouk; Hashim, Yumi Zuhanis Has-Yun; Salleh, Rohani; Hasim, Haslinda (Iranian Journal of Chemistry and Chemical Engineering, 2008)
Homogenizer and ultrasonicator that we call as mechanical methods were used in the lab scale production of alcohol free reduced glutathione (alcohol free GSH) from baker’s yeast. The study was done to determine the effects of specific parameters of the methods and the pH of the medium on the production of the GSH. The cell disruptions were run at a wide range of those parameters at the suitable common parameters of the methods. The disrupted cells suspension was then centrifuged at 12,000 rpm for 20 min and the GSH content in the supernatant was analyzed by taking the absorbance (A) value of the solution by spectrophotometer at 412 nm. The results obtained showed that the production of GSH was affected by the adjusted specific parameters of each method and the yield of production by the homogenizing and ultrasonic method was found 3.3 and 4.1 times, respectively, better than the yield of production by the unadjusted parameters. Ultrasonic method which produced 23.2 mg/L product was found 1.3 times better than the homogenizing method (18.5 mg/L) in producing the GSH. The result obtained from the lab scale study of the above mentioned mechanical methods showed that the implementation of them in the large scale production of the alcohol free GSH is possible.